Use of Aeromonas spp. as General Indicators of Antimicrobial Susceptibility among Bacteria in Aquatic Environments in Thailand - Usui, Masaru; Tagaki, Chie; Fukuda, Akira; Okubo, Torahiko; Boonla, Chanchai; Suzuki, Satoru; Seki, Kanako; Takada, Hideshige; Tamura, Yutaka (Frontiers in Microbiology, 2016)
Antimicrobials are widely used, not only for treating human infections, but also for treatment of livestock and in fish farms. Human habitats in Southeastern Asian countries are located in close proximity to aquatic environments. As such, the human populations within these regions are at risk of exposure to antimicrobial resistant bacteria (ARB), and thereby disseminating antimicrobial resistance genes (ARGs). In this study, we collected water samples from 15 sites (5 sites in Chao Phraya River, 2 sites at the mouth of Chao Phraya River, 3 sites in Ta Chin River, and 5 sites at city canals) and 12 sites (6 sites at city canals, 2 sites at chicken farms, 2 sites at pig farms, and 2 samples from sites at pig farms that were subsequently treated at a biogas plant) in Thailand in 2013 and 2014, respectively. In total, 117 Aeromonas spp. were isolated from the water samples, and these organisms exhibited various antimicrobial susceptibility profiles. Moreover, there was a significant correlation between the environmental concentration of tetracyclines and the rates of tetracycline resistance in the isolated Aeromonas spp. Notably, however, the concentration and resistance rates of tetracycline in samples derived from pig farms were higher than those of samples harvested from other aquatic environments. These findings suggest that the high concentrations of antimicrobials observed in these aquatic environments likely select for ARGs. Furthermore, they indicate that Aeromonas spp. comprise an effective marker for monitoring antimicrobial resistance in aquatic environments.